Studying physical and emotional aspects of self-care among patients with cancer referred to the chemotherapy ward of Shiraz Namazi Hospital - Vizeshfar, Fatemeh; Magharei, Mahboobe (Journal of Research in Biology, 2012)
Introduction: Being diagnosed with cancer is a painful experience for affected persons as well as their relatives. Both disease and it’s complication create a variety of symptoms that influence the way of self-care and facing patients with this matter in their prognosis. Objective: This research has been carried out with the aim to study the way of self-care and knowledge of patients under Chemotherapy regarding the physical and emotional aspects of self-care. Materials and Methods: This is a descriptive-analytical study and research population was consisting of patients under Chemotherapy referred to the Namazi Hospital among which, 134 persons were selected randomly. Results: Results indicated that, 101 cases (75.4%) were women with mean age of 46.8 years. Most of samples (64 persons, 47.8%) were illiterate. 113cases (84.3%) were married. Majority of samples (64 cases, 47.8%) were diagnosed with cancer and 72.4% of them used multi-drug treatment. 52.2% of samples had little knowledge about chemotherapy complication and 53.0% of them had no specific source of obtaining information. There was a statistically significant relation between physical care score and level of education P<0.0004). Discussion: According to the results of this research, educating cancer patients about self-care is very important and nurses should have more emphasis on teaching programs in order to promote quality of life (QOL) and knowledge of chemotherapy patients.